Cheap and Easy Synthesis of Highly Functionalized (Het)aryl Iodides via the Aromatic Finkelstein Reaction - Meyer-Eppler, Georg; Küchler, Lea; Tenten, Christina; Benkhäuser, Christian; Brück, Stefanie; Lützen, Arne (Synthesis, 2014)
Aryl iodides are superior coupling partners in cross-coupling reactions compared to the corresponding chlorides or bromides. Unfortunately, the iodides are much more expensive, if commercially available at all, than the other halides. Thus, it is often mandatory to transform the available bromides into the corresponding iodides. The copper-catalyzed aromatic Finkelstein reaction turned out to be the method of choice to prepare a number of highly functionalized iodo(het)aryls, including pyridines, 2,2′-bipyridines, and chiral compounds.
Keywords: halogen exchange; aromatic Finkelstein reaction; copper catalysis; aryl bromides; aryl iodides